The Cornwalls are gone - Patterson, James, 1947-; DuBois, Brendan (Little, Brown and Company, 2019)
Intelligence officer Amy Cornwall must use lethal tactics in open defiance of Army Command when a mysterious adversary kidnaps her family and gives her forty-eight hours to commit an unspeakable crime.